Logic and Value in Wittgenstein's Philosophy. (29th September 2020) - Stiers, Peter
Abstract: In Tractatus Logico‐Philosophicus (TLP), Wittgenstein gave ethics the same semantic status as logic. This paper first investigates this claim from the perspective of Wittgenstein's lifelong semantic framework. This reveals that ethical sentences are meaningless expressions, which can only be used to ostensively point out conditions of meaningfulness. Secondly, the paper assesses the implications of this conclusion for understanding the seven cryptic remarks on value and ethics in TLP. Using the connection between will and value in TLP and will and sentence interpretation in Philosophical Investigations, it is suggested that Wittgenstein held lifelong views on value and ethics.